Successfully reported this slideshow.
We use your LinkedIn profile and activity data to personalize ads and to show you more relevant ads. You can change your ad preferences anytime.
Actividades de razones algebraicas. Soluciones.
1. Efectúe las siguientes adiciones y sustracciones de razones algebraicas...
j1 =
3 Hx − yL
2 x y − x2 − y2
−
x
x2 − y2
−
1
x − y
;
−
5 x + 4 y
Hx − yL Hx + yL
k1 =
a bI6 a b − 5 b2M
I4 a2 − b2M
2
−
...
c2 =
1
1 + x
+
2 x
1 − x2
1
x
− 1 ;
1
x
d2 =
1
x
− x
1
x
+ x
1
x + 1
− 1 ;
H−1 + xL I1 + x2M
x
e2 = Hx + 1L
Hx + 1L2
x2 − ...
m2 =
a x + a y
b x − b y
×
x2 − 2 x y + y2
x2 − y2
×
b
a y − a
;
1
−1 + y
n2 =
x
y
−
y
x
x
y
+
y
x
x y
x2 + y2
;
Hx − yL H...
−
1
4
f3 = a +
a
b
ì
a2 − b2
b a − b2
;
a H1 + bL
a + b
g3 =
2 x
2 x + 3 y
+
3 y
2 x − 3 y
ì
2 x
2 x − 3 y
−
3 y
2 x + 3 y...
d4 =
1 +
2 x
y
1 +
H2 x−yL2
8 x y
×
y
2 x
+ 1 +
2 x
2 x+y
+
y
2 x−y
y
2 x+y
−
2 x
2 x−y
;
3
e4 =
1 +
1
a
a − 1
×
1
a
− a3
...
Upcoming SlideShare
Loading in …5
×

Ejercicios razones algebraicas y soluciones 2

4,499 views

Published on

Published in: Technology, Business
  • Be the first to comment

  • Be the first to like this

Ejercicios razones algebraicas y soluciones 2

  1. 1. Actividades de razones algebraicas. Soluciones. 1. Efectúe las siguientes adiciones y sustracciones de razones algebraicas: a1 = 3 − x 6 − 5 − y 20 − x − y 15 − x − 3 10 ; 1 60 H33 − 20 x + 7 yL b1 = 3 − x x + 2 x x − 1 − x − 1 3 x ; 2 I−5 + 7 x + x2M 3 H−1 + xL x c1 = a 3 b − a2 − 1 b2 + a2 + b a b − b2 a2 ; − −3 a2 + 3 a4 − 4 a3 b − 3 a b2 + 3 b4 3 a2 b2 d1 = x − 2 x − 1 + xHx − 1L x − 2 − x + 1 2 ; 6 − 5 x + x3 2 H−2 + xL H−1 + xL e1 = 3 Hx − 1L x2 − y2 − x + y y − x + x2 + y2 x2 − 2 x y + y2 ; 2 x3 + 3 y − 3 x H1 + yL + x2 H3 + 2 yL Hx − yL2 Hx + yL f1 = x − 2 6 x + 6 − x + 2 2 x + 2 + 3 − x 4 x + 4 ; − 7 12 g1 = 1 + x 9 x − x3 + 1 9 + x2 + 6 x − 1 6 x2 − 9 x − x3 ; 6 J2 + 7 − xN J−2 + 7 + xN H−3 + xL2 x H3 + xL2 h1 = x − y x + y − 3 x2 − y2 x2 + 2 x y + y2 ; − 2 x2 Hx + yL2 i1 = x4 + y4 Ix2 − y2M 2 + 4 x y x2 − y2 − Hx − yL2 x2 + 2 x y + y2 ; 2 x2 H4 x − 3 yL y Hx − yL2 Hx + yL2 1
  2. 2. j1 = 3 Hx − yL 2 x y − x2 − y2 − x x2 − y2 − 1 x − y ; − 5 x + 4 y Hx − yL Hx + yL k1 = a bI6 a b − 5 b2M I4 a2 − b2M 2 − b2 4 a2 + 4 a b + b2 − a2 + b2 4 a2 − b2 + a2 4 a2 − 4 a b + b2 ; a b H2 a − bL H2 a + bL l1 = 2 x − 3 Hx − 1L x2 − 3 x − x − H3 x + 1L x + 2 + 10 + H5 − xL Hx − 3L − Hx − 1L Hx + 2L x2 − x − 6 ; −2 + x x H2 + xL m1 = 2 − a2 I2 b2 + a2M + b2 H4 a + bL b2 − a2 + a Hb − aL − b Ha + bL2 a − b ; 2 a2 − 2 b2 + 4 a b2 + b3 − 4 a b3 − b4 Ha − bL Ha + bL n1 = x x2 − y2 + 1 Hx − yL2 − 1 Hx + yL2 − 4 x y Ix2 − y2M 2 ; x Hx − yL Hx + yL o1 = 1 + 5 y 3 x − x2 − 3 y2 x2 − 3 x y + 2 y2 + 10 y2 x − 2 y ; 2 y I−2 x2 + 15 x2 y + 5 y2 − 15 x y2M 3 x Hx − 2 yL Hx − yL p1 = x2 − 3 y3 x3 − x2 y − x y2 + y3 − 2 y2 x2 − 2 x y + y2 − 1 + x2 + y2 x2 − y2 ; x2 − 7 y3 Hx − yL2 Hx + yL q1 = x x2 − 2 x + 1 + x − 2 x2 − 1 − 4 x 2 x2 + 4 x + 2 ; 2 I1 − x + 2 x2M H−1 + xL2 H1 + xL2 2. Efectúe las siguientes multiplicaciones de razones algebraicas: a2 = 3 − 2 3 x + y2 9 x2 y; −3 x2 y I−9 + 2 x − 3 y2 M b2 = 3 4 x y−2 8 x − 2 9 y ; x H36 x − yL 6 y2 2
  3. 3. c2 = 1 1 + x + 2 x 1 − x2 1 x − 1 ; 1 x d2 = 1 x − x 1 x + x 1 x + 1 − 1 ; H−1 + xL I1 + x2M x e2 = Hx + 1L Hx + 1L2 x2 − 1 + x − 1 ; H1 + xL I2 − x + x2M −1 + x f2 = Hx + yL2 − z2 x2 − Hy + zL2 × x − y − z x + y − z ; 1 g2 = 1 + x 1 − x 1 − x 1 + x 1 − x2 − 1 − x2 x ; −1 + x x h2 = x3 − y3 x2 − y2 × x2 − 2 x y + y2 x2 − x y + y2 ; Hx − yL2 Ix2 + x y + y2M Hx + yL Ix2 − x y + y2M i2 = 16 x4 − 81 y4 4 x2 − 12 x y + 9 y2 × 4 x2 − 9 y2 16 x4 + 72 x2 y2 + 81 y4 ; H2 x + 3 yL2 4 x2 + 9 y2 j2 = 4 a2 − 4 Ha + 1L2 − a × a3 − 1 a3 − 2 a2 × a4 − 2 a3 x2 − 1 ; 4 H−1 + aL2 a H1 + aL H−1 + xL H1 + xL k2 = x2 − x − 2 x + 3 × x2 − Hy + zL2 x − y + z × 1 x − y − z ; H−2 + xL H1 + xL Hx + y + zL H3 + xL Hx − y + zL l2 = Hx − yL2 − z2 x + y + z × x2 − Hy + zL2 x − y + z × 1 x − y − z ; x − y − z 3
  4. 4. m2 = a x + a y b x − b y × x2 − 2 x y + y2 x2 − y2 × b a y − a ; 1 −1 + y n2 = x y − y x x y + y x x y x2 + y2 ; Hx − yL Hx + yL x y o2 = x y3 − 1 y2 x − y y + 2 x x − y − x2 x y − y2 ; 1 y2 p2 = x y − y x − 1 x y + y x − 1 y2 x − y − y3 x2 − x y ; Ix2 − x y − y2M Ix2 − x y + y2M x3 q2 = 3 Hx − 2 yL x2 − 2 x y + y2 × x2 − y2 12 x − 24 y ; x + y 4 Hx − yL 3. Efectúe las siguientes divisiones de razones algebraicas: a3 = a2 − 2 a b + b2 x2 − y2 ì a − b x − y ; a − b x + y b3 = a3 − 1 a3 + 1 ì a − 1 a + 1 ; 1 + a + a2 1 − a + a2 c3 = a5 + 32 a3 − b3 ì a + 2 a2 − b2 ; I16 − 8 a + 4 a2 − 2 a3 + a4M Ha + bL a2 + a b + b2 d3 = a2 − 5 a + 4 a2 + 7 a + 10 ì a − 4 a + 5 ; −1 + a 2 + a e3 = 3 a + 3 12 − 12 a ì Ha + 1L2 a2 − 1 ; 4
  5. 5. − 1 4 f3 = a + a b ì a2 − b2 b a − b2 ; a H1 + bL a + b g3 = 2 x 2 x + 3 y + 3 y 2 x − 3 y ì 2 x 2 x − 3 y − 3 y 2 x + 3 y ; 1 h3 = x2 − x + 1 x − 1 x2 ì x − 1 + 1 x ; H−1 + xL H1 + xL x i3 = x2 − 2 x y + y2 x2 + 2 x y + y2 ì x3 − 3 x2 y + 3 x y2 − y3 x2 − y2 ; 1 x + y j3 = x2 − 6 x + 9 x2 − x ì x2 − 4 x + 3 x2 − 4 x + 4 ì x2 − 5 x + 6 x2 − 2 x + 1 ; −2 + x x k3 = x−y x+y − x+y x−y x2−y2 x2+y2 − x2+y2 x2−y2 ì x y + y x ; 1 4. Efectúe las siguientes operaciones de razones algebraicas: a4 = 1 − x y 1 + x y × 1 + y x 1 − y x ; −1 b4 = 1 + 2 a + 1 a2 a + 3 + 2 a × a − 1 a 1 − 2 a + 1 a2 ; H1 + aL2 H−1 + aL H2 + aL c4 = 9 x2 + 4 y2 6 x y − 2 ì 9 x2 + 4 y2 6 x y + 2 × 3 x 3 x − 2 y ì 2 b 3 x + 2 y 2 ; 9 x2 4 b2 5
  6. 6. d4 = 1 + 2 x y 1 + H2 x−yL2 8 x y × y 2 x + 1 + 2 x 2 x+y + y 2 x−y y 2 x+y − 2 x 2 x−y ; 3 e4 = 1 + 1 a a − 1 × 1 a − a3 1 a3 + 1 ì a2 + a + 1 a + 1 a2 − 1 a ; − H1 + aL I1 + a2M I1 − a + a3M a I1 − a + a2M I1 + a + a2M f4 = Hx − yL2 − I 1 2 x − 2 yM 2 1 2 x−y y + x−2 y x ì I 1 2 x − 2 yM 2 − Hx − yL2 x+2 y x − 1 2 x+y y ; 1 g4 = J x y − 1N J x y + 1N J x2 y2 − 1N J x2 y2 + 1N ì J 2 x 3 y − 3 y 2 x N í J 3 y 2 x − 2 x 3 y N 5 Ix2+y2M+8 x y Hx−yL2−Hx+yL2 ; y I5 x2 + 8 x y + 5 y2M 4 x Ix2 + y2M h4 = x+2 y 2 − 1 4 x2+y2 x−2 y 2 x−2 y 2 + x2+4 y2 4 x+2 y 2 ì 2 x y 4 y2−x2 JJJ1 − x x+2 y N x2−4 y2 2 x N í J1 + 2 y x NN í J x 2 − x2+4 y2 2 x+4 y N ; 2 x y 6

×